Malondialdehyde-Induced Post-translational Modifications in Hemoglobin of Smokers by NanoLC-NSI/MS/MS Analysis - Chen, Hauh-Jyun Candy; Chen, Chau-Yi; Fang, Ya-Hsuan; Hung, Kai-Wei; Wu, Deng-Chyang (Journal of proteome research, 2022)
Malondialdehyde (MDA) is the most abundant α,β-unsaturated aldehyde generated from endogenous peroxidation of polyunsaturated fatty acids and is present in cigarette smoke. Post-translational modifications of blood hemoglobin can serve as biomarkers for exposure to chemicals. In this study, two types of MDA-induced modifications, the -propenal and the dihydropyridine (DHP), were identified at multiple sites in human hemoglobin digest by the high-resolution mass spectrometry. The -propenal and the DHP types of modification led to the increase of 54.0106 and 134.0368 amu, respectively, at the -terminal and lysine residues. Among the 21 MDA-modified peptides, 14 with dose-response to MDA concentrations were simultaneously quantified in study subjects by the nanoflow liquid chromatography nanoelectrospray ionization tandem mass spectrometry under selected reaction monitoring (nanoLC-NSI-MS/MS-SRM) without prior enrichment. The results showed that the modifications of the -propenal-type at α-Lys-11, α-Lys-16, α-Lys-61, β-Lys-8, and β-Lys-17, as well as the DHP-type at the α- -terminal valine, are significantly higher in hemoglobin isolated from the blood of smokers than in nonsmoking individuals. This is the first report to identify and quantify multiple sites of MDA-induced modifications in human hemoglobin from peripheral blood. Our results suggest that the MDA-derived modifications on hemoglobin might represent valuable biomarkers for MDA-induced protein damage.